(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Introduction: The advances in healthcare activities have resulted in generation of excessive amount of Biomedical waste. Improper waste management has a negative impact on the health of medical professionals, sanitary staff, general public and the environment in general. Objectives: To assess the Knowledge and Practice regarding biomedical waste management (BMWM) among healthcare workers (HCW) of government health facilities of rural Ghaziabad. Methodology: A cross-sectional study was conducted to assess the knowledge and practices regarding Bio-Medical waste, in rural blocks of the district Ghaziabad at C.H.C, P.H.C and Sub-centres. Health care worker (HCW) like Doctor, Nursing Staff, Laboratory technician and Sanitary staff working in the Health care facilities were selected for the Study. A total number of 122 HCW were selected, which included 27 Doctors, 75 Nurse, 06 Lab technician and 14 sanitary staff, using Proportional allocation scheme respectively. Result: The Knowledge regarding precautionary measure of BMWM was 82.7% and practice was 59.1% among the HCW. Multinomial regression between socio-demographic features of HCW and their practice regarding precautionary measures revealed that the practice was 6.045 (1.883- 19.411) times higher among graduates than diploma holders. Practice regarding precautionary measures was 13.542 (2.992-61.289) times higher among doctors as compared to nurses. Practice regarding the precautionary measure was 12.509 (3.302-47.380) times higher among the CHC staff and 3.059 (1.330- 7.038) times higher among PHC staff than sub-center staff. Conclusion: Level of knowledge and practice scores were unsatisfactory. Healthcare facilities should provide periodic training and adequate supplies for the waste handlers